The perception of undergraduates diploma students toward “Hexapodx Go!” : a game board approach of gamification on entomology - Yahutazi Chik; Suffina Long (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Hexapodx Go! is an educational board game which focuses on the different order of insects. The main objective of this board game is to provide an education on insects through entertainment. The number of players for Hexapodx Go! are ranging from two to six players, aged eight year old and above. The main goal of this game is for the players to collect as many insect cards as they can and to answer the Question Card and ultimately, reach the last pit stops. Hexapodx Go! gets its name from Hexapoda, a class of organism which possesses six legs. The board game consists of 127 hexagonal units where the outermost hexagon layer units of Hexapodx Go! contains ordinary insects with the lowest points and the innermost hexagon layer units of Hexapodx Go! contains rare species of insects with the highest points. One of the advantages of Hexapodx Go! is, it uses the entertainment aspects of the game for teaching and learning processes that can be used either in school or at home. This edutainment game also can increase competition among students and can be used as a helping tool in preparation for science subjects. In terms of the novelty of the Hexapodx Go!, there are fewer board games in the shape of a hexagon available and none are related to insects. A pilot study was conducted to determine the perception of the undergraduate diploma students toward Hexapodx Go! where most of the items received more than three on the average score, indicating positive feedback from the students. Meanwhile, in terms of recognition and award, this game board has been awarded with the Bronze Medal during Sarawak Invention, Innovation and Design Expo in 2019. Furthermore, in 2020, this game board received a gold award and the best poster award in the National Seminar on Research and Innovation in Education 2020 (e-SPeDIP2020). Therefore, Hexapodx Go! offers great possibilities for commercialization especially for the school and university students who have vast interest in insects.